2021
DOI: 10.3389/fvets.2021.747519
|View full text |Cite
|
Sign up to set email alerts
|

Application of Metabolomics in Diagnosis of Cow Mastitis: A Review

Abstract: Cow mastitis, with high incidence rate and complex cause of disease, is one of the main diseases that affect the development of dairy industry in the world. Clinical mastitis and subclinical mastitis caused by Staphylococcus aureus, Escherichia coli, Streptococcus, and other pathogens have a huge potential safety hazard to food safety and the rapid development of animal husbandry. The economic loss caused by cow mastitis is billions of dollars every year in the world. In recent years, the omics technology has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 91 publications
2
9
0
Order By: Relevance
“…Crucially, these metabolites were significantly elevated in MAPinfected cattle aged between 1-month and 19-months of age, compared to control cattle (Taylor et al, 2021). This stated some of our MAP associated metabolites have been also seen in a metabolomic assessment of mastitis infection (Hu et al, 2021). Indeed, out of 45 identified metabolites in this MAP study, 5 have been previously linked to mastitis.…”
Section: Discussionsupporting
confidence: 59%
“…Crucially, these metabolites were significantly elevated in MAPinfected cattle aged between 1-month and 19-months of age, compared to control cattle (Taylor et al, 2021). This stated some of our MAP associated metabolites have been also seen in a metabolomic assessment of mastitis infection (Hu et al, 2021). Indeed, out of 45 identified metabolites in this MAP study, 5 have been previously linked to mastitis.…”
Section: Discussionsupporting
confidence: 59%
“…Importantly, genome studies on mastitis-associated E. coli have been questioned by some investigators, who argue the need to simultaneously analyze the host-pathogen interaction ( Zadoks et al, 2011 ; Leimbach et al, 2017 ). For example, it is important to associate physiological traits with genomic data, including techniques such as dual RNA-Seq of the host and bacteria ( Westermann et al, 2016 , 2017 ), Tn-Seq to test virulence association of genes in vivo ( Opijnen et al, 2009 ; Peek et al, 2020 ), comparative SNP analysis of orthologous genes and intergenic regions ( Rocha et al, 2019 ), proteomics ( Zhang H. et al, 2018 ; Bathla et al, 2020 ), and metabolomics ( Tong et al, 2019 ; Hu et al, 2021 ).…”
Section: The Dilemma Of Mammary Pathogenic Escherichia Coli...mentioning
confidence: 99%
“…The prognostication of mastitis is an integral component of transition dairy cow management, and mastitis biomarkers are required for effective diagnosis and prognosis [ 42 ]. Our previous work showed that the ratio of neutrophils to platelets could be prognostic for mastitis [ 43 ], but the underlying mechanism was not clear.…”
Section: Discussionmentioning
confidence: 99%